Factor that Contributes to the Success of Green Technology Implementation in Malaysian Public Universities - Faathirah Jamaluddin; Amlus Ibrahim; Ahmad Yusni Bahaudin (International Journal of Supply Chain Management, 2018)
Abstract The purpose of this study is to investigate the relationship between technology and green technology implementation. Besides that, the author also determines the effect of government support as moderator to the relationship between technology and green technology implementation. The respondents for this study are three hundred and eighty-four (384) staff from Malaysian Public Universities in northern region. The primary data (using questionnaire) then were analysed using Statistical Packages for the Social Sciences (SPSS) by referring to Pearson Correlation, Hierarchical regression and Simple Slope analysis. The finding from Pearson Correlation shows that technology has a positive relationship with green technology implementation. Hierarchical Regression and Simple Slope analysis confirmed that government support moderates the relationship between technology and green technology implementation. Keywords green technology implementation, public university, moderator, hierarchical regression, government support, green supply chain